Wild Bee Pollen Diets Reveal Patterns of Seasonal Foraging Resources for Honey Bees - Wood, Thomas James; Kaplan, Ian; Szendrei, Zsofia (Frontiers in Ecology and Evolution, 2018)
Western honey bees (Apis mellifera) are dominant crop pollinators, and access to summer forage is a critical factor influencing colony health in agricultural landscapes. In many temperate agricultural regions, honey bees forage extensively from non-native plants during the summer, but it is unclear whether the use of these species is due to honey bee preference for these plants or is a result of their relative abundance. The foraging choices made by native bees that have evolved with native plants can reveal the seasonal availability of native plant pollens, and so we quantified the pollen collected by 181 wild bee species native to Michigan. Pollen was also trapped from honey bee colonies during the summer to confirm the peak period of non-native pollen collection in this region. Across the state, the generic richness of native pollens collected by wild bees peaked in May before linearly declining into September. Wild social and solitary bees collected a similar proportion of their pollen from non-native plants from April to July, but during August and September social bees collected a significantly greater proportion from non-natives. At a local scale, honey bees collected the majority of their pollen from non-native plants between 4 July and 21 August, with the same trend seen in both social and solitary bees. Across the region, a significantly greater proportion of the solitary bee species that peak during this time are specialists, most of which collect from native plant species that are little utilised by social bees for pollen, such as Dasiphora, Helianthus, Physalis and Vernonia. Our results suggest that Michigan has relatively few native flowering resources during the height of the summer, and that many of those which flower during this time are used primarily by specialised solitary bee species rather than the social bee community, including honey bees. As a result, non-native plant species with a late summer flowering phenology fill a forage gap and thus can contribute to the diet of both honey bees and generalist wild bees during this time, despite the well-documented negative impacts of these species on native plant communities.